Total Synthesis of Leupyrrins A1 and B1, Highly Potent Antifungal Agents from the Myxobacterium Sorangium cellulosum. Issue 14 (28th December 2016) - Thiede, Sebastian; Wosniok, Paul R.; Herkommer, Daniel; Debnar, Thomas; Tian, Maoqun; Wang, Tongtong; Schrempp, Michael; Menche, Dirk
Abstract: Full details on the design, elaboration, and application of efficient strategies for the high‐yielding total syntheses of leupyrrins A1 and B1, unique antifungal agents from the myxobacterium Sorangium cellulosum, are reported. A sequential zirconocene‐mediated diyne‐cyclization, and regioselective opening of the zirconacyclopentadiene intermediate enabled a concise entry into the unique dihydrofuran fragment, whereas another domino reaction was developed for the butyrolactone involving a one‐pot lactol opening, stereoselective aldehyde addition and in situ lactonization. Furthermore, an innovative sp 2 ‐sp 3 ‐cross‐coupling for pyrrole functionalization and an optimized HATU‐mediated amide coupling protocol of two elaborate fragments were established. In addition, an unusual protective group strategy, involving a Teoc‐acetonide protected amine in combination with tert ‐butyl and acetate esters, was successfully elaborated. These tactics and strategies are generally useful and may be also applied in the synthesis of other functionalized compounds. It is expected that the material which was obtained by these total syntheses will enable the further exploration of the biological profile of these potent antifungal agents. Abstract : The total syntheses of antifungal natural products, leupyrrins A1 and B1, were accomplished by an expedient and high‐yielding strategy. During this campaign, useful protocols were developed, including innovative one‐pot sequences to access the furan and butyrolactone moieties, an sp 2 ‐sp 3 ‐coupling for pyrrole functionalization, and an optimized HATU‐mediated amide coupling protocol.